Remote monitoring and control of wind turbine simulator (a1026-131) - Yin, Min Htet (2014)
The development and installation capacity of wind turbine system are growing rapidly. Most of the wind turbine systems are installed far from the rural area to avoid any obstacle in the wind direction. Therefore, remote monitoring and control of the wind turbine system is necessary to evaluate the efficiency and cost benefit of the wind turbine.